Strategies for Technology Integration in Vocational High Schools: Enhancing Teaching Quality and Student Engagement in the Digital Era - Arum Dwi Hastutiningsih; Asep Purwo Yudhi Utomo; Nuzulul Alifin Nur; Novia Suryadwanti; Minten Ayu Larassati (Universitas Negeri Yogyakarta, 2025)
Background: Integrating technology into vocational high school (SMK) curricula is essential for improving teaching quality and enhancing student engagement in the digital era. Despite national efforts to strengthen digital competence in education, many vocational schools continue to struggle with uneven technological readiness, limited infrastructure, and varying levels of digital skills among teachers. Understanding these challenges and identifying effective strategies for technology integration is therefore crucial, particularly in the context of SMK in Indonesia. Methods: This study employed a quantitative approach to examine teachers’ perceptions of technology integration in vocational education. Data were collected from vocational school teachers specializing in construction and building technology in Yogyakarta using a structured survey instrument. The analysis focused on identifying existing challenges, evaluating current technology utilization, and exploring teachers’ readiness to adopt innovative digital tools in the teaching–learning process. Results: Findings indicate that although most teachers consider current technology integration efforts adequate, significant issues persist, including limited technological infrastructure, uneven digital competencies, and resistance to pedagogical change. Teachers acknowledge that technology has strong potential to make learning more interactive and engaging, and many reported successfully encouraging students to incorporate digital tools into their tasks and projects. However, overall implementation remains inconsistent and requires further support. Conclusion: Technology integration in SMK shows promising progress but still requires targeted improvements to achieve optimal impact. Strengthening teacher training in innovative digital practices, enhancing technological infrastructure, and fostering supportive policies from school management and government are essential steps. These measures are expected to increase the competitiveness of SMK graduates in the labor market while promoting a more dynamic and interactive learning environment.